Feasibility of Using H3PO4/H2O2 in the Synthesis of Antimicrobial TiO2 Nanoporous Surfaces - Benjamín Valdez-Salas; Ernesto Beltrán-Partida (Bioinorganic Chemistry and Applications)
Ti6Al4V alloys are the primary materials used for clinical bone regeneration and restoration; however, they are substantially susceptible to biomaterial-related infections. Therefore, in the present work, we applied a controllable and stable oxidative nanopatterning strategy by applying H3PO4, a weaker dissociating acid, as a substitute for H2SO4 in the classical piranha reaction. The results suggest that our method acted as a concomitant platform to develop reproducible diameter-controlled TiO2 nanopores (NPs). Interestingly, our procedure illustrated stable temperature reactions without exothermic responses since the addition of mixture preparation to the nanopatterning reactions. The reactions were carried out for 30 min (NP14), 1 h (NP7), and 2 h (NP36), suggesting the formation of a thin nanopore layer as observed by Raman spectroscopy. Moreover, the antimicrobial activity revealed that NP7 could disrupt active microbial colonization for 2 h and 6 h. The phenotype configuration strikingly showed that NP7 does not alter the cell morphology, thus proposing a disruptive adhesion pathway instead of cellular lysis. Furthermore, preliminary assays suggested an early promoted osteoblasts viability in comparison to the control material. Our work opens a new path for the rationale design of nanobiomaterials with “intelligent surfaces” capable of decreasing microbial adhesion, increasing osteoblast viability, and being scalable for industrial transfer.